Evaluation of the Implementation of Teacing Factory in SMK Cordova Margoyoso Pati Central Java - Muhammad Zaenal Abidin; Rabiman Rabiman; Samsul Hadi; Alfat Kahaharsyah (Universitas Sultan Ageng Tirtayasa, 2025)
This study aims to determine the suitability of the implementation of the Teaching Factory at SMK Cordova Margoyoso Pati, Central Java, using the CIPP evaluation model (Context, Input, Process, Product). The background of this research is the limited synchronization between school-based industrial learning and real industrial practices, which has led to a gap between students’ competencies and industry needs. Initial observations found several problems such as inadequate facilities, limited involvement of industry partners, and a lack of systematic implementation guidelines for Teaching Factory. These issues have raised concerns regarding the effectiveness and sustainability of the program. This research uses a mixed-method approach with quantitative and qualitative methods conducted in an exploratory sequential manner. Data were collected through observation, interviews, questionnaires, and documentation during April–May 2024. Data validity was ensured through triangulation, as well as validity and reliability tests. The research subjects consisted of 30 students, 2 mentor teachers, and 1 school principal. The results show that the implementation of Teaching Factory at SMK Cordova Margoyoso in: 1) aspects of context, input, process, and product according to teachers and students are in the “very suitable” category. 2) accumulatively, these aspects fall into the “appropriate” category. However, several areas require further improvement, such as stronger collaboration with industry, regular updates to learning materials, and more structured evaluation procedures. Overall, the suitability of the Context, Input, Process, and Product aspects is in the appropriate category. Therefore, continuous improvement is necessary to optimize the quality and outcomes of the Teaching Factory implementation.Evaluation, CIPP Method, Teaching Factory, Vocational Education, Industrial Partnership